PENGARUH SOFTWARE MYOB ACCOUNTING TERHADAP HASIL BELAJAR AKUNTANSI SISWA DI SMA MUHAMMADIYAH 6 PALEMBANG - Nur Fadilah Mudmainnah; Deskoni; Rusmin AR (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2017)
This research aims to determine the influence significant between software MYOB accounting and microsoft excel toward eleven grades student’s learning outcomes of Accounting subject in Senior High School Muhammadiyah 6 Palembang. This is an experimental research using true experimental control group design pretest post-test form. The population were all of social eleven grade students of Senior High School Muhammadiyah 6 Palembang. The data were got through test and observation. The result of experimental group’s observation interpreted into the activity’s researcher was so good. T-test was used to test the hypothesis. The calculation gained t calculate > t tabel, so that Ho was rejected and Ha was accepted. Thus, there was influence significant between software MYOB accounting and Microsoft Excel toward eleven grades student’s learning outcomes of Accounting subject in Senior High School Muhammadiyah 6 Palembang. There were some student experience difficulty when operated software MYOB accounting, and there were account names in software MYOB accounting which actually can’t modification because the database have been locked so will experience difficulty for adjusting stage.